2016
DOI: 10.1590/1806-9061-2016-0289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stocking Density on the Performance and Immunity of 1- to 14-d- Old Broiler Chicks

Abstract: The current experiment was conducted to evaluate the effect of stocking density (SD) on the performance and immunity of 1-to 14-d-old broilers. A total of 1836 one-day-old Cobb 500 broilers were housed at four different SD (30, 60, 90 and 120 chicks/m 2 ). Body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) were estimated on d 2, 5, 8, 11 and 14. Relative lymphoid organ weights, maternal antibody titers against IBV, IBD and NDV, and stress indicators were estimated on d 3, 6, 9 and 12.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
(68 reference statements)
5
22
1
3
Order By: Relevance
“…Although there are different studies investigating the effects of the stocking density on various behavioral and physiological changes in rodents (Arakawa, 2005;Smith et al, 2005;Whitaker et al, 2007), domestic hens (Simsek et al, 2014;Eugen et al, 2019), quail (Ayasan et al, 2000;Toplu and Fidan, 2008;Bahsi et al, 2016), fishes (Jia et al, 2016;Rayhan et al, 2018), pigs (Cornale et al, 2015;Kim et al, 2016;Larsen et al, 2018), broiler (Qaid et al, 2016;Li et al, 2019) and primates (Yamagiwa, 1999;Duncan et al, 2013), no studies have investigated its effect on antioxidant capacity. In the present study, therefore, the effect of the stocking density on the antioxidant capacity in the rats was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are different studies investigating the effects of the stocking density on various behavioral and physiological changes in rodents (Arakawa, 2005;Smith et al, 2005;Whitaker et al, 2007), domestic hens (Simsek et al, 2014;Eugen et al, 2019), quail (Ayasan et al, 2000;Toplu and Fidan, 2008;Bahsi et al, 2016), fishes (Jia et al, 2016;Rayhan et al, 2018), pigs (Cornale et al, 2015;Kim et al, 2016;Larsen et al, 2018), broiler (Qaid et al, 2016;Li et al, 2019) and primates (Yamagiwa, 1999;Duncan et al, 2013), no studies have investigated its effect on antioxidant capacity. In the present study, therefore, the effect of the stocking density on the antioxidant capacity in the rats was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Houshmand et al (2012) found that there has been no difference between stocking density groups of 10 and 16 broiler chickens m -2 on blood glucose levels and H/L ratios. In contrast Qaid et al (2016) found that except blood glucose levels stress indicators as decreasing H/L levels and increasing heterophyl levels showed that there is an impact of stocking density on stress of the broiler chickens. Azzam and Gogary (2015) also reported that there has been no change on blood glucose levels of chickens reared at stocking densities of 11.90 birds m -2 and 16.66 birds m -2 .…”
Section: Introductionmentioning
confidence: 83%
“…Males were slaughtered at the 20 th week where females were at 16 th week which were the suitable and the present application at the time of the study. This rearing period is as well up to date and used by the industry still (Housmand et al, 2012;Qaid et al, 2016).…”
Section: Methodsmentioning
confidence: 99%